Preparation of high purity SiO2 from Rice Husk - Mohd Razif Mohd Shariff (Universiti Malaysia Perlis, 2009)
A high purity silicon dioxide (97.08%) was obtained by atmosphere thermal decomposition of the acetic acid leached rice husk at 800°C for 15 minutes. Leaching process parameters such as pH of the acid solution, leaching temperature and time were varied. Analysis of all the acid leached thermal decomposed samples were made using Scanning Electron Microscopy with Energy Dispersive X-ray Spectrometer (SEM-EDS), X-ray Diffractrometer (XRD) and Atomic Absorption Spectrometer (AAS).The result from XRD showed the samples were amorphous silica as indicated by broaden peaks around (2Ө = 22°). The SEM microgram indicates almost complete formation of SiO2 in thermal decomposition. The EDX analysis results showed the highest SiO2 (97.08%) for pH 4 acid acetic leached solution at room temperature for 3 days without stirring. The AAS results of trace impurities content of Ca, Mg, K and Na in the silicon dioxide extract, high percent leachible efficiency of acetic acid than 90% for all the inorganic compound.